A grave in my garden. Genetic identification of Spanish civil war victims buried in two mass graves in Espinosa de los Monteros (Burgos, Spain). (December 2015) - Núñez, Carolina; Baeta, Miriam; Palencia-Madrid, Leire; Herrasti, Lourdes; Etxeberria, Francisco; de Pancorbo, Marian M.
Abstract: We report the genetic study of 13 victims of the Spanish Civil war buried in two mass graves in Espinosa de los Monteros (Burgos, Spain). The grave with the highest number of individuals (grave 1; N = 9) was found in the garden of a private house of the village. The other grave (grave 2) was only 200 m away and the remains of four women were unexpectedly found. Skeletal remains, mainly teeth, were better preserved in graves 1 than 2. Mean DNA extraction yield was 0.17 ng/μl. In order to carry out the genetic identification of the remains, buccal swabs from 11 family relatives were available. The choice of genetic markers analyzed relied on the different levels of biological kinship to be elucidated. For 75% of the post-mortem samples, ≥12 autosomal STR profiles were obtained. Y chromosome STRs, as well as mitochondrial DNA control region, were also analyzed in order to study paternal and maternal lineages, respectively. Besides, X chromosome STRs were typed in one case to verify a paternal grandmother–granddaughter relationship. We successfully identified 9 of 13 individuals buried in the two mass graves of Espinosa de los Monteros, 6 in grave 1 and 3 in grave 2. The search of further relatives' samples would be of interest to perform more comparative analyses, and eventually do not leave any of the victims without a name.